Human papilloma virus‐associated squamous cell carcinoma of the larynx in an 18‐year‐old woman. Issue 4 (27th December 2018) - Hotz, Michel‐André; Christen, Brigitte; Sahli, Roland; Arnold, Andreas Michael
Abstract: Background: Human papilloma virus (HPV)‐associated malignancies are considered to be sexually transmitted diseases. Methods: We report a HPV‐positive larynx cancer in an 18‐year‐old female clarinet player, despite vaccination with the quadrivalent HPV‐6‐11‐16‐18‐vaccine Gardasil (Merck Sharp & Dohme Corp., West Point, Pennsylvania). The patient showed no evidence of genito‐oral infection but showed some evidence for oral‐oral HPV transmission through the sharing of saliva‐infested clarinet mouthpieces. A right vocal cord lesion of benign appearance was removed via free margin resection. Results: Histopathology revealed a microinvasive squamous cell carcinoma inside a zone of high‐grade dysplasia that was positive for HPV‐45. No tumor recurrence was observed during a 4‐year follow‐up evaluation. Conclusion: Benign lesion appearance and quadrivalent HPV vaccine status do not exclude HPV‐associated malignancies. In our patient, the Gardasil vaccine did not provide crossover protection against HPV 45 infection. HPV‐associated disease may not necessarily be transmitted via sexual practice patterns alone.